Comparative Analysis of Local Taxes in The Surabaya City Area - Melly Yuliana; Vincentia Devina Setyawati (CONTABILITA : Journal of Accounting and Finance, 2025)
The Regional Government requires funding from Regional Original Income (PAD) to carry out equitable development in order to improve community welfare. Funding can come from regional taxes such as Hotel Tax, Restaurant Tax, Entertainment Tax, Street Lighting Tax which can be allocated evenly for regional development. Taxpayers are still not fully aware and contribute to paying regional taxes. This study aims to determine the comparison of regional taxes in the Surabaya City area for the period 2019-2023. This research approach uses a descriptive qualitative approach method through case studies by collecting data through observation, interviews, and documentation studies. The results obtained from this study are that the highest regional tax revenues are in the Central Surabaya area, followed by the second in the East Surabaya area, followed by the South Surabaya area, West Surabaya and the smallest tax is in the North Surabaya area. The types of taxes with the highest revenues in the City of Surabaya can be ranked as follows, the first is restaurant tax, the second is hotel tax, the third is parking tax, the fourth is entertainment tax, and the smallest is street lighting tax for the Surabaya city area.